Perlindungan Hukum Konsumen atas Penjualan Properti Menggunakan Sistem Pre Project Selling - Rafi Erdian Wibowo; Gunawan Djajaputra (Universitas Ekasakti, 2024)
The pre-project selling system implemented by housing developers often results in consumer losses. When consumers suffer losses, they have the right to claim compensation from the respective developers. These compensation claims are governed by the legal protection framework outlined in the Consumer Protection Act and the Civil Code. This research aims to identify the legal consequences arising from the pre-project selling system conducted by housing developers and to evaluate the legal protection available to consumers in this context. The type of research used is normative research, which is based on the study of theories and applicable legal rules. This normative research also serves to provide legal arguments in situations of voids, ambiguities, and conflicts of norms. Thus, this research is considered very important as policy input to provide justice for the community.